PENDEKATAN STEGO-KRIPTO MODE CIPHER BLOCK CHAINING UNTUK PENGAMANAN INFORMASI PADA CITRA DIGITAL - Vera Wati; Hanifatus Sa’diyah; Dony Ariyus (LPPM Nusa Mandiri, 2020)
The digital image can be one of the media for information security. The contents of information have an important value of effectiveness, one of which is as a support in decision making. Then the information needs to be done to safeguard the authority of parties who are not responsible. Such security can utilize Steganography and Cryptography (Stego-Crypto). The method used combines Stego-Crypto by randomizing information using Cipher Block Chaining (CBC) then the encryption results are secured through digital images. Based on the test results by measuring the capacity of information on the image produces test data if CBC can process characters in uppercase, spaces and other characters and the results of plaintext and ciphertext produce a ratio of 1: 2, but the LSB performance only accommodates characters depending on the number of sizes on digital image. Testing by evaluating the difference in pixel histogram, when viewed with an invisible not very visible difference, but the insertion of messages with 100-200 characters causes the addition of the average image size on stego images larger than 1: 4, the value of 1 from the original image. Besides, testing with the help of communication media, stego images or encrypted images is able to use email to send stego images because LSB is sensitive to the process of resizing images